Audit Delay In Industrial Firms: An Analysis Of Firm Size, Profitability, And Solvency - Purwantoro Purwantoro; Entot Suhartono (Jurnal Telekomunikasi dan Informatika, 2023)
Audit execution time is the time required to complete the audit, computed from the conclusion of the accounting cycle to the date documented in the report. Timely financial reporting is essential for making decisions. Extended audit delays diminish the significance and worth of the data in the financial statements. Knowing the factors that contribute to audit delays is critical to ensuring the timely and appropriate provision of financial information. The objective of this research is to investigate the potential impact of company size, profitability (ROA), and solvency (DER) on the audit delays. The study involved 112 companies spanning different sectors, all of which were listed on the Indonesian Stock Exchange between 2019 and 2022. Multiple linear regression analysis was employed as the analytical method. The findings revealed that firm size and profitability (ROA) had a notable negative effect on audit delays, whereas solvency (DER) had a significant positive impact on audit delays. This research can help companies and auditors identify factors that contribute to audit delays and take steps to improve the timeliness and relevance of financial reporting.